2021
DOI: 10.1002/cncr.33867
|View full text |Cite
|
Sign up to set email alerts
|

Population screening to identify women at risk for hereditary breast cancer syndromes: The path forward or the road not taken?

Abstract: Population screening of family cancer history to identify women at risk for a hereditary breast cancer syndrome is feasible and effectively identifies high‐risk women who are eligible for genetic counseling referral. However, uptake of counseling is low among referred women, and there is a critical need to develop multilevel interventions that promote uptake of genetic counseling in diverse groups of patients identified through population‐based screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…27,28,30 Studies have found that such digital tools effectively identify at-risk patients who would have been overlooked. 25,27,30,[32][33][34][35] Importantly, patients report high levels of satisfaction with digital tools in genomics care. 20,27,33,[36][37][38] Thus, these digital tools show promise for helping increase access to guideline-recommended hereditary cancer risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…27,28,30 Studies have found that such digital tools effectively identify at-risk patients who would have been overlooked. 25,27,30,[32][33][34][35] Importantly, patients report high levels of satisfaction with digital tools in genomics care. 20,27,33,[36][37][38] Thus, these digital tools show promise for helping increase access to guideline-recommended hereditary cancer risk assessment.…”
Section: Introductionmentioning
confidence: 99%